Visual outcomes, patient satisfaction and spectacle independence with a trifocal diffractive intraocular lens - Kretz, Florian Tobias Alwin; Choi, Chul Y.; Müller, Matthias; Gerl, Matthias; Gerl, Ralf Helmar; Auffarth, Gerd U. (Korean journal of ophthalmology, 2016)
Kretz FT, et al. Korean J Ophthalmol. 2016 Jun;30(3):180-191. https://doi.org/10.3341/kjo.2016.30.3.180